(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ornaments are the marker of culture, tradition, status, passion and personality. Sometimes those heavy ornaments cause trauma and recurrent infection in the piercing-hole of ear, which may lead to enlargement of the piercing hole. To restore the, enlarged piercing hole; in Ayurved we have techniques like scraping and suturing of the piercing-hole edges, which is also practiced by modern advanced surgery. Kshara (alkali) is an Anushashtra; it performs the Lekhana (scraping), Chhedana (excision), Bhedana (incision), Ropana (healing) and also ceases the bleeding. Because of these properties, Kshara can also be used to restore the enlarged piercing-hole of ear. The Kshara causes ulceration of the piercing-edges and induces healing through the inflammation, proliferation and remodeling phases. There were inflammation, secretion and gradually the piercing hole healed. Based on this concept, we have tried to restore the piercing hole of the ear through Ksharakarma and an ideal protocol is made for this procedure.